A Percutaneous Knotless Technique for SLAP Repair - Tennent, Duncan (Arthrosc Tech, 2016)
We describe a percutaneous technique for repair of type II SLAP lesions. Through the Neviaser portal, a spinal needle is used to pass a FiberStick suture (Arthrex, Naples, FL) through the labrum to create 2 mattress sutures that are secured with PushLock anchors (Arthrex). This technique is simple, reproducible, and knotless and requires no cannulas. At the end of the procedure, minimal suture material remains in the joint.